Methods for forecasting in the Danish National Transport model - Rich, Jeppe; Hansen, Allan Steen (Proceedings from the Annual Transport Conference at Aalborg University, 2010)
The present paper is concerned with the forecasting methodology applied in the new Danish national model. The new national model will apply two forecast methods depending on the type of demand model considered. For models which can be estimated on the basis of TU data and is further covered by register data from Statistic Denmark, a prototypical sample enumeration approach will be used. For models, where this is not the case, a matrix model approach will be used. Typically, this will be the case for models where respondents include foreigners. In this case we do not have register data for the respondents and the TU data will only cover the Danish segment. The key to do forecasting based on a prototypical sample enumeration methodology is to apply a population synthesiser, which can forecast the population profile. By combining the population forecast with the micro- survey, it is possible to derive expansion factors which can be used to up-scale the demand model. The “expansion” is used to lifts the TU data base to a representative population level. The paper will first in brief terms discuss the choice of forecast methodology. Hereafter, we will consider the design of the population synthesiser in some details. Finally, we will test the proposed population synthesiser by back-casting.